2012
DOI: 10.5121/ijcseit.2012.2205
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Acceptance of Web-Based Training System: Using Extended Utaut and Structural Equation Modeling

Abstract: Advancement in information system leads organizations to apply e-learning system to train their employees in order to enhance its performance. In this respect, applying web based training will enable the organization to train their employees quickly, efficiently and effectively anywhere at any time. This research aims to extend Unified Theory of Acceptance and Use Technology (UTAUT) using some factors such flexibility of web based training system, system interactivity and system enjoyment, in order to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 18 publications
7
34
0
Order By: Relevance
“…A handful of studies (e.g. Alrawashdeh et al, 2012;Schaper & Pervan, 2007;Urumsah et al, investigating the factors influencing consumers to use the e-services of Indonesian airlines, Urumsah et al (2011) found that a consumer's access to and use of the services were influenced by the good-quality technical infrastructures and support provided by the airlines.…”
Section: H4: Facilitating Conditions Have a Positive And Significant mentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of studies (e.g. Alrawashdeh et al, 2012;Schaper & Pervan, 2007;Urumsah et al, investigating the factors influencing consumers to use the e-services of Indonesian airlines, Urumsah et al (2011) found that a consumer's access to and use of the services were influenced by the good-quality technical infrastructures and support provided by the airlines.…”
Section: H4: Facilitating Conditions Have a Positive And Significant mentioning
confidence: 99%
“…2011) on IS/IT adoption have also supported the positive and significant impact of facilitating conditions on effort expectancy. For example, while examining the factors impacting the acceptance of a web-based training system among employees in Jordan,Alrawashdeh et al (2012) found a newly detected significant relationship between facilitating conditions and effort expectancy. Similarly, exploring ICT acceptance and utilization by Australian occupational therapists,Schaper and Pervan (2007) found a positive and significant relationship between facilitating conditions and effort expectancy.…”
mentioning
confidence: 99%
“…SI consists of a positive or negative influence of family and close friends and accordingly the probability of adoption changes. Previous studies associated with Smartphones have also indicated the same about for technology adoption (Slade et al, 2013;Fehrenbacher, 2013;Alrawashdeh et al, 2012;Admiraal et al, 2013;Raman and Don, 2013;Venkatesh et al, 2012).…”
Section: Social Influence (Si)mentioning
confidence: 74%
“…PE is the strongest among all constructs used to assess the technology acceptance and usage (Adell, 2010;Pahnila et al, 2011;Alrawashdeh et al, 2012;Venkatesh et al, 2003;Oshlyansky et al, 2007;Raman and Don, 2013;Pahnila et al, 2011;Yu and Conway, 2012;Venkatesh et al, 2012). A student not only expects the smartphone device to improve the academic scores, but also the overall academic performance (Yang et al, 2010).…”
Section: Performance Expectancy (Pe)mentioning
confidence: 99%
“…Adapting performance expectancy to mobile learning suggests that users will find it useful because it enables learners to accomplish learning activities effectively and flexible (Masrek & Shahibi, 2019). It is one of the most significant determinants for technology adoption (Mohd Azli et al, 2019;Amzauorou & Oubaha, 2018) and use behaviour (Duarte & Pinho, 2019;Alrawashdeh et al, 2012;Yu, 2012). This construct consists of five criteria: extrinsic motivation, perceived usefulness, outcome expectations, job fit and relative advantage (Wong et al 2020).…”
Section: Performance Expectancymentioning
confidence: 99%